Review on dynamic group data sharing in cloud environment - Easwaramoorthy, Sathishkumar; Chunduru, Anilkumar; Moorthy, Usha; B, Sravankumar (International Journal of Engineering and Technology, 2018)
Information sharing or exchange of data within entities plays a significant role in cloud storage. In cloud computing, a robust and practical methodology is developed which can be utilized by cloud users for sharing information among multiple group members in the cloud with lowered maintenance and management costs. Furthermore, a service provider in the cloud does not share data with anyone other than the Trusted Third Party (TTP) sources due to the semi-trusted characteristics of the cloud. In this way, there is no global security mechanism for dynamic group data sharing over the cloud. Subsequently, the Cloud Service Providers (CSPs) can convey different services to cloud users through powerful data centres. Hence, data is secured through the validation of users in the cloud. Meanwhile, CSPs should offer outsourced security assurance for data file sharing. Assuring privacy in data sharing is still a critical issue due to continuous change in cloud users, particularly, for unauthenticated or third party users because of the risk of collusion attacks. However, security concerns turn into a major restraint as outsourcing storage data is perhaps a delicate concern for cloud providers. Additionally, sharing information in a multi-proprietary approach while protecting information and individual security to the data from unauthorized or third party users is still a challenging task as there is a frequent change in cloud members. In this regard, previous studies are reviewed and discussed which are related to dynamic group data sharing using cloud computing.